Determination of crystallization of waxy crude and the influence of diluents - Abdul Kadir, Abdul Aziz; Ismail, Issham (Faculty of Chemical & Natural Resources Engineering, UTM Skudai, 1997)
This paper discusses the determination of crude oils behavior with high wax content. The crude oil begins to behave as pseudo-plastic fluid at temperature 10oC above its onset crystallization temperature (WAT). This is the temperature that characterizes the waxing potential of crude oils. In this study, laboratory tests that are used to determine the cloud point and quantify the deposition of paraffin wax were investigated. The influence of petroleum-based diluents on the onset crystallization point have also been studied. Two waxy crude samples from PM8 oilfields were used in this study. Accurate measurement of WAT will help to determine the optimum condition without facing the wax problem. Application of diluents to reduce the wax formation is restricted to only low wax content of crude oil.